Wireless Sensor Networks: Architectures and Protocols - Callaway, Jr (CRC Press, 2009)
Because they provide practical machine-to-machine communication at a very low cost, the popularity of wireless sensor networks is expected to skyrocket in the next few years, duplicating the recent explosion of wireless LANs.